SEAL OF METROPOLITAN OF KYIV KYRYL (1225–1233) FROM HALYCH - KOVAL, Ihor (Halych. Scientific work collection, 2017)
The author of the article introduces to the scientific world still unknown sphragistic item / lead seal of Kyryl I, the metropolitan of Kyiv (1225–1233), found near the wall of the Assumption Cathedral in Halych. The author also makes an attempt to establish its appearance in the capital of the Halych land in connection with the military and political events in 1228.